A measurement of the CP asymmetry difference between [Lambda]+c→pK−K+ and pπ−π+ decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Esen, Sevda; Gerick, David; Grabowski, Jascha; Grünberg, Oliver; et al. (Journal of high energy physics, 2018)
The difference between the CP asymmetries in the decays Λ c + → pK−K+ and Λ c + → pπ−π+ is presented. Proton-proton collision data taken at centre-of-mass energies of 7 and 8 TeV collected by the LHCb detector in 2011 and 2012 are used, corresponding to an integrated luminosity of 3 fb−1. The Λ c + candidates are reconstructed as part of the Λ b 0 → Λ c + μ−X decay chain. In order to maximize the cancellation of production and detection asymmetries in the difference, the final-state kinematic distributions of the two samples are aligned by applying phase-space-dependent weights to the Λ c + → pπ−π+ sample. This alters the definition of the integrated CP asymmetry to A CP wgt (pπ−π+). Both samples are corrected for reconstruction and selection efficiencies across the five-dimensional Λ c + decay phase space. The difference in CP asymmetries is found to be ΔAwgtCP=ACP(pK−K+)−AwgtCP(pπ−π+)=(0.30±0.91±0.61) %,ΔACPwgt=ACP(pK−K+)−ACPwgt(pπ−π+)=(0.30±0.91±0.61) %, \begin{array}{c}\hfill \Delta {A}_{CP}^{\mathrm{wgt}}={A}_{CP}\left(p{K}^{-}{K}^{+}\right) - {A}_{CP}^{\mathrm{wgt}}\left(p{\pi}^{-}{\pi}^{+}\right)\hfill \\ {}\hfill = \left(0.30 \pm 0.91 \pm 0.61\right)\ \%,\hfill \end{array} where the first uncertainty is statistical and the second is systematic. Open image in new window